COVID-19 Pandemic Planning and Preparedness for Institutions Serving People Living With Disabilities in South Africa: An Opportunity For Continued Service and Food Security - Mzini, Loraine Boitumelo (LB) (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
On March 11, 2020, the World Health Organization declared the COVID-19 outbreak as pandemic just about three months after its emergence in December 2019 in Wuhan, China. The outbreak of COVID-19 launched the world into a public health crisis, impacting families, schools, and communities in unprecedented ways. This paper examines the existence of pandemic planning and preparedness for institutions serving PLWD in order to ensure continued service for its users. The research also analyses the considerations applied to address the challenges that a pandemic will present. This study comes at an opportune moment when institutions serving PLWD become overwhelmed and face possible closure of their facilities. As COVID-19 continues to have wide-reaching impacts across the globe, it is important to understand how persons with disabilities are uniquely impacted by the pandemic, including health, education, and food security. Method: A qualitative study was considered complemented by telephone interviews in two facilities (Evaton and Katlehong) serving PLWD were used as a case study. Results: The paper concludes that adequate pandemic planning and preparedness in response to COVID-19 are critical to saving both lives and livelihoods and continuous service delivery. The respondents articulated a need for inclusive strategies where disabled people are involved as consultants and partners, not just as users. Conclusion: Diligent planning was found to be essential. The results highlight the role of the institutions serving PLWD in being effective and supporting service delivery and food security.